Prediction of the Number of Language Users Ngapak (Penginyongan) Using Linier and Logistic Model - Ambar Sari Nurahmandhani; Dewi Rifattul Qonita; Agung Prabowo (International Journal of Ethno-Sciences and Education Research, 2021)
The abstract should summarize the context, content and conclusions of the paper in less than 200-300 words. It should not contain any references or displayed equations. Typeset the abstract in 10pt Times Roman. A maximum of 4-6 key words or phrases must be given that will be useful for retrieval and indexing. The key words must be separated by commas and should not include acronyms.